Culăcimea în RSS Moldovenească: mit și realitate [Articol] - Șișcanu, Ion (Lexon-Prim, 2023)
The term “kulak” emerged in the Tsarist Russia’s villages before 1861 reform. A “kulak” was the peasant who got wealthy by enslaving fellow peasants and who held the entire peasant community “in his fist”, i.e. dependent on him. During 1918-1920, in Bolshevik Russia, against the background of the “war communism”, this social category had disappeared. In the period of late 1920s, in the USSR, any well-to-do household could be labelled as a Kulak’s property. In 1930, the Soviet administration elaborated “The Kulak’s household criteria”. In the Moldavian SSR, although there was a lack of indicators any existence of Kulak’s households, similar to those in the USSR, the authorities took up the issue of fighting Kulakism immediately after the occupation of Bessarabia. “The policy of terminating Kulakism as a class” and the repressions were mainly directed against the broad stratum of the peasantry. The main criterion for the assessment of “kulak” households had a political character, elaborated by the structures of the Bolshevik Party and, above all, by the Ministry of State Security of the Moldavian SSR.
Kulakism in the Moldovian SSR: myth and realiti
Keywords: collectivization; kulak; Moldavian SSR; deportation; deportare; culaci